2019
DOI: 10.1021/acs.chemrestox.8b00345
|View full text |Cite|
|
Sign up to set email alerts
|

The Multiple Biological Targets of Hops and Bioactive Compounds

Abstract: Botanical dietary supplements for women's health are increasingly popular. Older women tend to take botanical supplements such as hops as natural alternatives to traditional hormone therapy to relieve menopausal symptoms. Especially extracts from spent hops, the plant material remaining after beer brewing, are enriched in bioactive prenylated flavonoids that correlate with the health benefits of the plant. The chalcone xanthohumol (XH) is the major prenylated flavonoid in spent hops. Other less abundant but im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 91 publications
1
92
0
Order By: Relevance
“…The potential for hops as a source of bioactives, including polyphenols, is considerable [14], leading to a number of potential targets that may be affected via hormonal mechanisms, as some of the bioactives can mimic estrogen, whilst others may function via antioxidant mechanisms or through altering metabolism to enhance the metabolism of xenobiotics and even regulate lipid metabolism.…”
Section: Hopsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential for hops as a source of bioactives, including polyphenols, is considerable [14], leading to a number of potential targets that may be affected via hormonal mechanisms, as some of the bioactives can mimic estrogen, whilst others may function via antioxidant mechanisms or through altering metabolism to enhance the metabolism of xenobiotics and even regulate lipid metabolism.…”
Section: Hopsmentioning
confidence: 99%
“…This has led to considerable interest in the hop, not only for its flavor and aromatic properties in beer, but as a potential nutritional supplement. This is because hops, which generally refers to the female flower cones of the plant, have been found to be a rich source of prenylated phenols, including chalcones and flavonoids (some of which are classed phytoestrogens) [14]. It has been proposed that the estrogen-modulating effects of hops and their extracts are due to the effects of them being antagonists and binding to the estrogen receptor, preventing the action of estrogen, as well as the potential to inhibit aromatase, which is the rate limiting step in the synthesis of estrone and estradiol (E 2 ).…”
Section: Hopsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Choi et al claimed that b-naphthoflavone, as a nontoxic flavonoid, can induce the detoxification potential of the representative detoxification enzyme cytochrome P4501A1 (Chuang et al 2012). Subsequently, Bolton et al reported that a potent AhR agonist 6-Prenylnarigenin in hops, resulting in a selective up-regulation of the P450 1A1-mediated estrogen detoxification pathway (Bolton et al 2019). Of note, some flavonoids that bind to AhR elicit antagonism rather than increase CYP1 activity.…”
Section: The Role Of Dietary Flavonoids As Ahr Ligands In Cancermentioning
confidence: 99%
“…Humulus lupulus (hop) is a dioecious twining bine in the Cannabaceae family of flowering plants with a long history of cultivation (Neve, 1991;Moir, 2000) for various uses including medicine (as reviewed by Ososki and Kennelly, 2003;Bolton et al, 2019) and animal fodder (Siragusa et al, 2008), but is most commonly known as a flavoring agent in the brewing industry. The quest for complex taste and aromas in the rapidly expanding craft brewing industry has placed increasing demands on breeders to produce new varieties of plants with specific desirable traits as well as disease resistance (Kavalier et al, 2011;Easterling et al, 2018;Yan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%